Acute kidney function and morphology following topload administration of recombinant hemoglobin solution - Martucci, Alexandre Fabricio [UNESP]; Ferreira Abreu Martucci, Ana Carolina Carvalho [UNESP]; Cabrales, Pedro; Nascimento, Paulo do [UNESP]; Intaglietta, Marcos; Tsai, Amy G.; Machado Castiglia, Yara Marcondes [UNESP] (Taylor & Francis Ltd, 2017)
There is a 0.138% incidence of adverse reactions related to blood transfusion. Transfusion-related acute lung injury, immunosuppression, fever, pathogen transmission, and hemolytic transfusion reactions are the most common ones. Synthetic oxygen carriers have been developed to deal with blood shortages and for use in the field where stored blood was not available. They were also designed to be pathogen free, including unknown viruses. In this study, we used Male Golden Syrian Hamsters implemented with a dorsal window chamber to determine how infusion of three different, genetically crosslinked recombinant acellular hemoglobin (rHb) solutions with different oxygen affinities and nitric oxide kinetics affect mean arterial pressure (MAP), heart rate (HR), kidney function, and kidney structure. We found that the administration of all three rHb solutions caused mild hypertension and bradycardia 30minutes after infusion. However, acute changes in glomerular filtration rate (GFR) were not detected, even though histological analysis was performed 72hours after treatment revealed some structural changes. All the rHb solutions resulted in hypertension 30minutes after a 10% topload administration. Regardless of their properties, the presence of acellular Hb causes significant alterations to kidney tissue.
Keywords: Blood substitutes; glomerular filtration rate; fluorescein-isothiocyanate sinistrin; acute kidney injury